The Effects of Metabolic Work Rate and Ambient Environment on Physiological Tolerance Times While Wearing Explosive and Chemical Personal Protective Equipment. (19th March 2015) - Costello, Joseph T.; Stewart, Kelly L.; Stewart, Ian B.
Abstract : This study evaluated the physiological tolerance times when wearing explosive and chemical (>35 kg) personal protective equipment (PPE) in simulated environmental extremes across a range of differing work intensities. Twelve healthy males undertook nine trials which involved walking on a treadmill at 2.5, 4, and 5.5 km·h −1 in the following environmental conditions, 21, 30, and 37°C wet bulb globe temperature (WBGT). Participants exercised for 60 min or until volitional fatigue, core temperature reached 39°C, or heart rate exceeded 90% of maximum. Tolerance time, core temperature, skin temperature, mean body temperature, heart rate, and body mass loss were measured. Exercise time was reduced in the higher WBGT environments (WBGT37 < WBGT30 < WBGT21; P < 0.05) and work intensities (5.5 < 4 < 2.5 km·h −1 ; P < 0.001). The majority of trials (85/108; 78.7%) were terminated due to participant's heart rate exceeding 90% of their maximum. A total of eight trials (7.4%) lasted the full duration. Only nine (8.3%) trials were terminated due to volitional fatigue and six (5.6%) due to core temperatures in excess of 39°C. These results demonstrate that physiological tolerance times are influenced by the external environment and workload and that cardiovascular strain is the limiting factor to work tolerance when wearing this heavy multilayered PPE.